Measurement of neutral current cross sections at high Bjorken-x with the ZEUS detector at HERA - Chekanov, S; Derrick, M; Magill, S; Miglioranzi, S; Musgrave, B; Nicholass, D; Repond, J; Yoshida, R; Mattingly, M; Pavel, N; Molina, A; Antonelli, S; et al. (2007)
A new method is employed to measure the neutral current cross section up to Bjorken-x values of one with the ZEUS detector at HERA using an integrated luminosity of 65.1 pb-1 for e+p collisions and 16.7 pb-1 for e-p collisions at √s = 318 GeV and 38.6 pb-1 for e+p collisions at √s = 300 GeV. Cross sections have been extracted for Q2 ≥648 GeV2 and are compared to predictions using different parton density functions. For the highest x bins, the data have a tendency to lie above the expectations using recent parton density function parametrizations. © Springer-Verlag Berlin Heidelberg 2007.